Communication strategies used by junior and senior teachers in teaching English at secondary school - Nurul Mutia Utami (Center for Humanities and Innovation Studies, 2018)
This research aims to find out the types of communication strategies used by the junior and senior teacher in teaching English. This study also explores the differences and similarities of communication strategies used by junior and senior teachers in teaching English. This research employed descriptive qualitative research. The participants of this research were two English teachers in Makassar. The data of this research were collected by employing observation and interview. The researchers adapted and modified Tarone’s (1977), Bialystok’s (1983), and Dörnyei and Scott’s taxonomy (1995a, 1995b) of communication strategies in identifying the data. The obtained data were analyzed in three major phases namely data collection, data reduction, data display, and conclude. The results of this research revealed that there were fifteen types of strategies used by the junior teacher and eleven types of strategies used by the senior teacher in teaching English. The junior teacher used topic avoidance, literal translation, code-switching, retrieval, other-repair, fillers, self-repetition, other-repetition, direct/indirect appeal for help, asking for repetition, asking for clarification, asking for confirmation, interpretive summary, comprehension check, and mime/gestures. The senior teacher used the literal translation, restructuring, code-switching, fillers, selfrepetition, other-repetition, direct/indirect appeal for help, asking for repetition, asking for confirmation, comprehension check, and mime/gestures.